Analisa Tegangan Pipa Pada Sistem Ballast Kapal Tugboat 24 Meter Menggunakan AutoPIPE - Hendra Saputra; Nurzain Miftakhul Jannah (Jurnal Teknologi dan Riset Terapan (JATRA), 2021)
Ballast system on ship especially on tugboats aims to maintain ship stability and to help the ship sail in safe condition. The design of ballast system, the used of pipe in this system is necessary to do pipe stress analysis to make sure the pipe is safe to support the system. This study aims to analyze the pipe stress happened in the system. The pipe stress analysis focuses on sustained and hope stress. On this study, we use AutoPIPE software to create the pipe model and to analyze the pipe stress. ASME B31.3 standard (piping process) is used as code standard on pipe stress analysis. For the purpose of pipe modelling, the piping of ballast system is divided into two piping lines. The piping lines No.1 is the line from seachest to water ballast tank and piping line No.2 is line from water ballast tank to overboard. The temperature used in the analysis is 30°C or at normal seawater temperatures, while the working pressure of the ballast system used is 72.52 Psi for each line number. The result of this study shown that the sustained stress and hoop stress that occur in piping line No.1 are 8,466 Psi and 3,732 Psi, respectively and in piping line No.2 are 7,020 Psi and 1,328 Psi, respectively. The result also shown that the pipe stress for both lines are still below the material allowable stress, where the allowable stress of the material is 20,000 Psi.